2017
DOI: 10.3389/fphar.2017.00495
|View full text |Cite
|
Sign up to set email alerts
|

Potential New Therapies for Pediatric Diffuse Intrinsic Pontine Glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) is an extensively invasive malignancy with infiltration into other regions of the brainstem. Although large numbers of specific targeted therapies have been tested, no significant progress has been made in treating these high-grade gliomas. Therefore, the identification of new therapeutic approaches is of great importance for the development of more effective treatments. This article reviews the conventional therapies and new potential therapeutic approaches for DIPG, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 143 publications
(170 reference statements)
2
50
0
1
Order By: Relevance
“…Consistent with molecular findings from tumor-based studies, two markers in this panel were shown to correlate with overall survival (OS) in patients with diffuse midline glioma in this cohort -the presence of an H3F3A/HIST1H3B mutation was predictive of poor overall survival consistent with the specific entity of H3K27M-mutant diffuse midline glioma, where as an IDH1 mutation predicted better OS (Pan et al, 2019). Targeted therapies for these alterations are currently undergoing clinical trials (Long et al, 2017). Histone 3 allele-specific PCR and single gene Sanger sequencing assays have been developed to aid the diagnosis of H3K27M-mutant diffuse midline gliomas, with 87.5% clinical sensitivity for CSF cfDNA when compared to tissue testing .…”
Section: Brainstem Tumorssupporting
confidence: 79%
“…Consistent with molecular findings from tumor-based studies, two markers in this panel were shown to correlate with overall survival (OS) in patients with diffuse midline glioma in this cohort -the presence of an H3F3A/HIST1H3B mutation was predictive of poor overall survival consistent with the specific entity of H3K27M-mutant diffuse midline glioma, where as an IDH1 mutation predicted better OS (Pan et al, 2019). Targeted therapies for these alterations are currently undergoing clinical trials (Long et al, 2017). Histone 3 allele-specific PCR and single gene Sanger sequencing assays have been developed to aid the diagnosis of H3K27M-mutant diffuse midline gliomas, with 87.5% clinical sensitivity for CSF cfDNA when compared to tissue testing .…”
Section: Brainstem Tumorssupporting
confidence: 79%
“…H3K27 acetylation (H3K27ac) and H3K27 tri-methylation (H3K27me3) act like a molecular switch [42] ( Table 1). Indeed, groundbreaking studies by Lewis et al showed that H3.3K27M increased total H3K27ac and reduced total H3K27me3, to induce glioma formation and subsequent tumor progression in a brainstem glioma model.…”
Section: Acetylationmentioning
confidence: 99%
“…En un estudio fase II publicado recientemente en pacientes con glioblastoma IDH nativo recurrente se observó en un paciente con enfermedad multifocal portador de la mutación H2K27, una reducción tumoral de 85% en una lesión y 76% de la lesión secundaria 12 . Actualmente se encuentra en reclutamiento 2 estudios fase II para el tratamiento con ONC201 de gliomas difusos H3k27M en adultos con enfermedad recurrente (NCT03295396/ NCT02525692), además de extensa investigación preclínica es búsqueda de nuevas moléculas 13 .…”
Section: Discussionunclassified